2016
DOI: 10.4236/ojpm.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Liquid versus Ice Slurry Ingestion on Core Temperature during Simulated Mining Conditions

Abstract: Miners in Australia frequently perform physically demanding work under high ambient temperatures and humidity, often whilst wearing personal protective equipment, leading to heat-related illnesses. This study investigated effects of replacing 100% and 50% sweat losses with 5% carbohydrate liquid or ice-slurry solution on core temperature during simulated mining conditions. Five randomized treadmill trials were performed with: no fluid replacement (NF), 100% (100 ICE) and 50% (50 ICE) sweat loss replaced with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This process transfers a large amount of internal heat from the body to the ingested ice (latent heat of fusion), creating a more powerful cooling effect than cold fluid ( Vanden Hoek et al , 2004 ; Siegel et al , 2010 ). For example, during walking exercise in mild ( Maté et al , 2016 ) and extreme heat ( Watkins et al , 2018 ) in full PPE, ingestion of ice slurry is shown to reduce core body temperature prior to and during activity. The positive effects of ice slurry seem to ease after ~20 min during activity, but reingestion prolonged its protective effect ( Maté et al , 2016 ; Watkins et al , 2018 ).…”
Section: Covid-19 Ppe and Occupational Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This process transfers a large amount of internal heat from the body to the ingested ice (latent heat of fusion), creating a more powerful cooling effect than cold fluid ( Vanden Hoek et al , 2004 ; Siegel et al , 2010 ). For example, during walking exercise in mild ( Maté et al , 2016 ) and extreme heat ( Watkins et al , 2018 ) in full PPE, ingestion of ice slurry is shown to reduce core body temperature prior to and during activity. The positive effects of ice slurry seem to ease after ~20 min during activity, but reingestion prolonged its protective effect ( Maté et al , 2016 ; Watkins et al , 2018 ).…”
Section: Covid-19 Ppe and Occupational Heat Stressmentioning
confidence: 99%
“…For example, during walking exercise in mild ( Maté et al , 2016 ) and extreme heat ( Watkins et al , 2018 ) in full PPE, ingestion of ice slurry is shown to reduce core body temperature prior to and during activity. The positive effects of ice slurry seem to ease after ~20 min during activity, but reingestion prolonged its protective effect ( Maté et al , 2016 ; Watkins et al , 2018 ). Fourth, cooling of the hands in running water or ice water buckets, even while wearing protective gloves, provides a meaningful cooling effect during recovery breaks ( House and Tipton, 2005 ).…”
Section: Covid-19 Ppe and Occupational Heat Stressmentioning
confidence: 99%
“…Protecting workers’ health while maintaining labor productivity is vital [ 16 , 17 , 18 ] and has driven many researchers to investigate the effectiveness of different heat mitigation strategies [ 19 , 20 ]. Specifically, heat mitigation strategies such as planned breaks [ 21 ], use of personal cooling vests [ 22 , 23 ], ice slurry consumption [ 22 , 24 ], optimized clothing [ 25 ], and ventilated garments [ 26 , 27 ] were previously tested in lab settings for mitigating the OH-strain experienced by individuals performing physical work (typically exercise). However, there is limited knowledge regarding the capacity of these heat mitigation strategies to protect workers’ health and labor productivity in occupational settings, taking into account real-life work-related parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a condition in which the human body exhibits inadequate physiological capacity to tolerate excess heat generated within and/or outside the body (Kjellstrom et al, 2016b). The risk and effect of heat stress on workers emanates from environmental, individual and occupational related heat exposure risks factors (Haines & Patz, 2004;Maté et al, 2016;Parsons, 2014;Schulte & Chun, 2009).…”
Section: Introductionmentioning
confidence: 99%